Emotional Inteligence in The Qur’an: Study of The Story of The Prophet Musa and Khidr - Ermayani, Tri (Universitas Muhammadiyah Surakarta, 2025)
The concept of emotional intelligence was first proposed by Peter Salovey and John D. Mayer (1990) in their scientific article entitled